Tumor suppression in human skin carcinoma cells by chromosome 15 transfer or thrombospondin-1 overexpression through halted tumor vascularization - Bleuel, Kerstin; Fusenig, Norbert; Boukamp, Petra (Proceedings of the National Academy of Sciences of the United States of America, 1999)
The development of skin carcinomas presently is believed to be correlated with mutations in the p53 tumor suppressor and ras gene as well as with the loss of chromosome 9. We now demonstrate that, in addition, loss of chromosome 15 may be a relevant genetic defect. Reintroduction of an extra copy of chromosome 15, but not chromosome 4, into the human skin carcinoma SCL-I cells, lacking one copy of each chromosome, resulted in tumor suppression after s.c. injection in mice. Transfection with thrombospondin-1 (TSP-1), mapped to 15q15, induced the same tumor suppression without affecting cell proliferation in vitro or in vivo. Halted tumors remained as small cysts encapsulated by surrounding stroma and blood vessels. These cysts were characterized by increased TSP-1 matrix deposition at the tumor/stroma border and a complete lack of tumor vascularization. Coinjection of TSP-1 antisense oligonucleotides drastically reduced TSP-1 expression and almost completely abolished matrix deposition at the tumor/stroma border. As a consequence, the tumor phenotype reverted to a well vascularized, progressively expanding, solid carcinoma indistinguishable from that induced by the untransfected SCL-I cells. Thus, these data strongly suggest TSP-1 as a potential tumor suppressor on chromosome 15. The data further propose an unexpected mechanism of TSP-1-mediated tumor suppression. Instead of interfering with angiogenesis in general, in this system TSP-1 acts as a matrix barrier at the tumor/stroma border, which, by halting tumor vascularization, prevents tumor cell invasion and, thus, tumor expansion.